Prevalence and characteristics of participants in Dry January 2024: findings from a general population survey in France - Louis-Ferdinand Lespine; Louis-Ferdinand Lespine; Diane François; Julie Haesebaert; Jean-Michel Delile; Myriam Savy; Benjamin Tubiana-Rey; Mickael Naassila; Julia de Ternay; Benjamin Rolland; Benjamin Rolland; Benjamin Rolland (Frontiers Media S.A., 2024)
BackgroundDry January is a one-month alcohol abstinence challenge for the general population running since 2013 in the United Kingdom, and 2020 in France. Dry January has gained increasing popularity among the public, but studies assessing the individual characteristics associated with awareness and participation remain sparse.MethodsUsing quota sampling, a representative sample of 5,000 French adults completed an online cross-sectional survey between 8 and 17th January 2024. Chi-square tests and binary logistic regressions were used to explore demographic and alcohol-related characteristics associated with awareness of the Dry January campaign as well as participation.ResultsAmong 4,075 past-year alcohol users, 2,468 (61%) were aware of the "Dry January" campaign, of whom 497 (20%) were participants (12% of all alcohol users). Extrapolated to the entire adult French population, this corresponds to an estimated 4.5 million people participating in the Dry January 2024. Awareness was comparable between genders and across age groups, but was greater among individuals with higher occupational status, and lower among those living in Eastern regions of France. Individuals aware of the campaign were more likely to self-evaluate their drinking as "at risk" and to report high-risk consumption. Participation rates did not differ by gender, occupational status, or region but decreased with age. Compared to non-participants, Dry January participants were more likely to self-identify their drinking as at-risk, to be concerned about health-related effects of alcohol, to be concerned about their control (or lack thereof) over drinking, and to report hazardous use or possible alcohol use disorder. However, no evidence was found for an association between high-risk consumption based on AUDIT-C and participation. Among participants, aiming for reduction (vs. abstinence) and official registration (vs. unofficial participation), were associated with worsened alcohol-related measures.ConclusionThis study indicates a stable level of awareness, but encouraging participation in Dry January in France. The results also confirm that temporary alcohol abstinence campaigns primarily attract high-risk drinkers and individuals reporting harmful consequences related to alcohol.